Economic analysis of ashwagandha (Withania somnifera L. Dunal) based agroforestry land-use systems in Mid Hills of Western Himalayas - Verma, K.S.; Thakur, N.S. (Indian Journal of Agroforestry, 2020)
Studies on effect of tree-crop combinations and nitrogen levels on economic returns from Withania somnifera L. Dunal, based agroforestry systems were carried out during 2004-2005 and 2005-2006, in experimental farm of Department of Silviculture and Agroforestry, Dr. Y S Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh. W somnifera was grown in association with Prunus persica (Peach), Grewia optiva, Morus alba and Setaria sphacelata. The tree-crop combinations (agroforestry systems) formed were, Peach + Grewia + Setaria + W. somnifera, Peach + Morus + Setaria + W. somnifera, Peach + Setaria + W. somnifera, Grewia + Setaria + W. somnifera, Morus + Setaria + W. somnifera, and W. somnifera as sole crop. Three nitrogen doses applied to W. somnifera were 40, 80 and 120 kg/ha. The net returns were calculated on financial (farmer's land) and economic (rented land) basis. The maximum net financial returns amounting to Rs. 11377/ha accrued from ashwahandha roots, were obtained under Peach + grewia + Setaria followed by Rs. 11321/ha under Peach + Morus + Setaria. The Peach and Setaria under Peach + Setaria agroforestry system gave maximum net returns to the tune of Rs. 39691/ha, followed by Rs. 36772/ha from Peach, Morus and Setaria under Peach + Morus + Setaria system. The agroforestry system, Peach + Setaria + W. somnifera gave maximum net returns of Rs. 50116/ha, followed Paech + Morus + Setaria + W. somnifera with net returns amounting to Rs. 48093/ha. The maximum benefit:cost ratio (B:C ratio) values to the tune of 3.87 were obtained from Morus + Setaria + W. somnifera system on farmers land (financial perspective), whereas, it was 1.60 from Peach + Setaria + W. somnifera system assuming the enterprise have been taken on rented land (economic perspective).